Essays on the Economics of Regional Climate Policy. - Burmeister, Johannes (My University, 2019)
This cumulative thesis quantifies the economic effects of regional climate policy. The regional scale of the analyses covers the state and national level. It consists of three papers, each of which is a chapter of the dissertation. The first paper introduces the first theory based and consistent non-survey regionalization method for national Input-Output tables. It can be regarded as a supplemental paper in order to create the data base for the second paper. The second paper quantifies the income and employment effects of the renewable energy expansion plans of the state of Schleswig-Holstein for the year 2030 by means of a computable general equilibrium (CGE) analysis. Finally, the third paper assesses the optimal national carbon price floor levels for individual EU countries within the European Union Emissions Trading System (EU ETS).
Keywords: Umweltschutz; Umweltpolitik; Regionalpolitik; Klima; Klimapolitik; Erneuerbare Energie; Regionalwirtschaft; Emissionshandel; Kohlendioxid; Wertschöpfung; Wirtschaftsgeografie; Modellierung; Fallbeispiel; Kohlendioxidminderung; Gravitationsmodell